KUALITAS PELAYANAN MUTASI PEGAWAI - Dwisasti, T. Ardi (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Mutations Quality Service Employees. The purpose of research is to analyze the quality of service of a mutation in the civil service in the province of Riau. The study population are civil servants who receive services BKPPD mutations in Riau Province, consists of 836 employees. By using the formula Slovin obtained a total sample of 90 civil servants mutations service recipient. The technique of collecting data using questionnaires and interviews. The data were analyzed using descriptive analysis. The study concluded that the average civil servants who receive services mutations are less satisfied with the service BKPPD Riau province, in particular on: the procedure, the fulfillment of technical requirements, process time, equality and justice handling of the mutation process, competence, guarantee certainty of schedule and feeling safe.